Treatment of Strip Perforation Using Root MTA: A Case Report - Froughreyhani, Mohammad; Salem Milani, Amin; Barakatein, Behnaz; Shiezadeh, Vahhab (Iranian Endodontic Journal, 2013)
Root perforations are an undesired complication of endodontic treatment which result in loss of integrity of the root, and adversely affect the prognosis of the treatment. Recently, Iranian mineral trioxide aggregate (Root MTA) has been introduced as an ideal material for perforation repair. In this article a successful repair of strip root perforation of mandibular molar using Root MTA is presented with 15-month follow-up. This case suggests that Root MTA may be a substitute material for the treatment of strip perforation; however, more clinical studies with larger sample size and longer follow-ups are needed.